KALIUM DI MULTIDRUG RESISTANCE TUBERKULOSIS DENGAN PENGOBATAN KANAMISIN (Potassium in Multidrug Resistance Tuberculosis with Kanamycin) - J.B. Suparyatmo; B. Rina AS; Harsini Harsini; Sukma Sukma (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Multidrug-Resistant Tuberculosis (MDR-TB) with bacillary resistance to at least isoniazid and rifampicin in vitro is a worldwidephenomenon. For MDR-TB second-line antibiotic agents that are more potent and more toxic must be used. . One of them is kanamycingiven intravenously every day for six (6) months therapy. Kanamycin is nephrotoxic and can lead to hypokalemia. This study is carriedout to know the comparison between the potasium level before and after kanamycin therapy (2, 4 and 6 months after therapy). Thisstudy is a cohort retrospective design, comprising 34 patients who had a potassium baseline before therapy in Moewardi Hospital,Surakarta from January 2011–August 2012. The characteristic data included: age, sex, weight and comorbidity. The potassium levelafter 2, 4 and 6 months post therapy was compared with the potassium data baseline using One Way ANOVA test with p< 0.05, CI95%. The difference between the potassium level after 6 months therapy and potassium baseline was significant, p < 0.05. However,the difference of the kalium level after 2 and 4 months after therapy was not significant, p > 0.05. Hypokalemia occurred in 6 patientsafter 2 months therapy, 8 patients after 4 months therapy and 3 patients after 6 months therapy. There was a significant differencebetween the potassium level after 6 months therapy and potassium baseline. Further study should be continued to know the existenceof hypokalemia among MDR-TB patients